Analisis Masalah Kualitas pada M/C Crank Shaft M2 dengan Menggunakan Tool Capability Process di PT XYZ, Pegangsaan Dua, Jakarta - Gidion Karo Karo; Jessie Deborah R. Makapedua (JIEMS (Journal of Industrial Engineering and Management Systems), 2017)
Process Capability is a tool that is often used in the process of quality improvement, especially for process improvement. This study uses a process capability analysis on crank shaft production line 2 for motorcycles. By using normality test data and process capability indices for calculation of Cp/Cpk, shows that most of the data obtained are not normally distributed, so need to transform the data into normal, which can then be followed by the calculation of process capability. For the calculation of Cp/Cpk, it was found that there were some machines that still need to get tight control to meet the specification. It shows that mass production is still less stable. In order to meet the specifications, it is necessary to improve the quality of the repair process to reduce the variation in the process.Keywords: Process Capability, Quality Control, Process Improvement